“La Loca” y “La Victima”: An Analysis of Penalizing Gender Non-Conformity After Death - Avalos, Susana (Homicide studies, 2024)
The United States experienced a record number of homicides against transgender victims in 2020, six of which occurred in Puerto Rico. Of the victims, five were trans women, and one was a trans man. Through case-study analysis, we explore how gender nonconformity is stigmatized within the context of Puerto Rico. Using storyline analysis of the language used by offenders, news media, and police, several themes emerged: (1) framing trans people as deceitful; (2) deadnaming, misgendering, and victim-blaming, and (3) community advocacy for the murder victims. Using the framework of hetero-cis-normativity, we explore how hetero-cis-normative biases may explain why negative attitudes toward trans individuals vary.